2020
DOI: 10.1038/s41559-020-1261-z
|View full text |Cite
|
Sign up to set email alerts
|

Neanderthal introgression reintroduced functional ancestral alleles lost in Eurasian populations

Abstract: Neanderthal ancestry remains across modern Eurasian genomes, and introgressed sequences influence diverse phenotypes. Here we demonstrate that introgressed sequences reintroduced thousands of ancestral alleles that were lost in Eurasian populations prior to introgression. Our simulations and variant effect predictions argue that these reintroduced alleles (RAs) are more likely to be tolerated by modern humans than introgressed Neanderthal-derived alleles (NDAs) due to their distinct evolutionary histories. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…The largest set included all variants with evidence of introgression in any Eurasian population according to Sprime 36 ( N = 900,902, Methods); this set will be referred to as “introgressed variants” throughout the manuscript. This set includes not only high-confidence Neanderthal-origin introgressed variants, but also ancestral alleles lost in Africans that were reintroduced to Eurasians through archaic introgression 5 , variants with origins in other archaic hominins, such as Denisovans, and possibly variants tightly linked to introgressed haplotypes that arose in Eurasians shortly after introgression. The most stringent and high-confidence sets include Neanderthal-introgressed alleles that are observed in Europeans and explicitly match either the Altai genome ( N = 138,774) or the Vindija genome ( N = 167,927, see Methods); these sets will be referred to as “Altai-matching” and “Vindija-matching” introgressed variants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest set included all variants with evidence of introgression in any Eurasian population according to Sprime 36 ( N = 900,902, Methods); this set will be referred to as “introgressed variants” throughout the manuscript. This set includes not only high-confidence Neanderthal-origin introgressed variants, but also ancestral alleles lost in Africans that were reintroduced to Eurasians through archaic introgression 5 , variants with origins in other archaic hominins, such as Denisovans, and possibly variants tightly linked to introgressed haplotypes that arose in Eurasians shortly after introgression. The most stringent and high-confidence sets include Neanderthal-introgressed alleles that are observed in Europeans and explicitly match either the Altai genome ( N = 138,774) or the Vindija genome ( N = 167,927, see Methods); these sets will be referred to as “Altai-matching” and “Vindija-matching” introgressed variants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, nearly all Eurasians have ~2% Neanderthal ancestry resulting from interbreeding events that occurred shortly after their ancestors left Africa 1 , 2 . Analyses of available genome-wide association studies and large-scale biobank data revealed that alleles of Neanderthal ancestry are associated with diverse traits in modern Eurasians 1 , 3 5 . However, due to limited phenotype data and technical challenges quantifying the associations between archaic alleles and traits 5 , 6 , previous studies have not comprehensively characterized the genome-wide influence of Neanderthal introgression on modern human diseases and traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these associations may be influenced by linked non-Neanderthal alleles 140 . For example, in addition to alleles of Neanderthal origin, introgression also reintroduced ancestral alleles that were lost in modern Eurasian populations prior to interbreeding (for example, in the out-of-Africa bottleneck) 141 . Some introgressed alleles may have initially lessened adverse effects from migration to northern climates, dietary changes and introduction to novel pathogens 117 , 142 , 143 .…”
Section: Recent Human Demographic Historymentioning
confidence: 99%
“…Nevertheless, we provide a proof of concept that applying computational and experimental functional genomics approaches enables researchers to assay the gene regulatory function of archaic alleles in modern human cells. Recently, MPRA data have been used to show that ancestral alleles reintroduced by Neanderthal introgression have activity levels similar to non-introgressed variants, while Neanderthal derived alleles are depleted for regulatory activity compared to reintroduced ancestral alleles [57]. Interestingly, in the dataset we considered, all functionally validated Neanderthal alleles led to increased gene expression.…”
Section: Discussionmentioning
confidence: 99%